Parametric Analysis and Photo Elastic Experiment of Stress Concentration Factor and Its Mitigation in Rectangular Plate with Opposite V- notches Subjected to In-Plane Loading - Shubhrata Nagpal (New Approaches in Engineering Research Vol. 16, 2021)
Flat plates weakened by presence of sharp V-notches subject to axial loads are analyzed by various researchers. Attempts towards mitigation of stress concentration factor due to V-notches are limited. In the present work, mitigation of the stress distribution due to notch under in-plane static loading in rectangular isotropic plates using area reduction method. The variations of stress concentration factor (SCF) for different b/A ratios, depth of V-notch to plate width is established, for subtended angle, 2\(α\), of V notch 60o, 90o, 120o, and 150o. Mitigation in stress concentration factor (SCF) around main notch has been carried out by introducing auxiliary semi circular notches around V-notch. Effect of various geometric parameters on the stress mitigation is also studied. The optimum size and position of auxiliary semicircular notches has been obtained. The work has been carried out using finite element analysis and two dimensional photo elasticity method. The results are shown in graphical forms and discussed. The mitigation thus obtained in Stress Concentration Factor due to introduction of semicircular notches in the vicinity is encouraging.